Circulating levels of neurotrophic factors are unchanged in patients with Parkinson's disease - Natalia Pessoa Rocha (Arquivos de Neuro-Psiquiatria)
ABSTRACT There is great evidence linking neurotrophic factor (NF) dysfunction with Parkinson's disease (PD) pathophysiology. This study was conducted to evaluate plasma levels of NFs and their possible associations with clinical symptoms in PD. For this purpose, 40 PD patients and 25 controls were subjected to a clinical evaluation and peripheral blood draw. Plasma levels of brain-derived neurotrophic factor (BDNF), pro-BDNF, neurotrophin 3, neurotrophin 4, nerve growth, glial cell line-derived neurotrophic factor and ciliary neurotrophic factor were measured by enzyme-linked immunosorbent assay. There was no significant difference between PD patients and controls regarding the plasma levels of the evaluated NFs. In addition, NF levels were not associated with disease duration, degree of motor or functional impairment, cognitive performance or severity of depressive symptoms. In conclusion, although NFs may play relevant roles in the pathophysiology of PD, the circulating levels of these molecules are not necessarily changed in patients with PD.